2022
DOI: 10.1590/fst.51820
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the caffeine-containing beverages available in the local markets, and development of a real energy drink based on the date fruit

Abstract: Globally, tea, coffee, soft and energy drinks are daily consumed as a source of caffeine. Energy drinks gained a great public and scientific issues, thus this study assessed the caffeine content in some caffeine-containing beverages. Given the increasing demand for newly formulated healthy drinks, the date fruit (Phoenix dactylifera L. cv. Siwi) was used to develop a fruit-energy drink as an alternative for the energy drinks. Results displayed that the coffee addition even to 80 mg/250 mL, did not significantl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 34 publications
1
8
0
Order By: Relevance
“…Apart from the enrichment of self-contained flavoring substances, the additives could also introduce new aroma components into CTLs. Coffee and cocoa contain abundant caffeine and theobromine, respectively, which give tobacco leaves fragrant aroma of coffee, cocoa, and nut (Gutierrez et al, 2022;Mostafa, 2022). It is consistent with the results of sensory quality.…”
Section: Aroma Components Analysissupporting
confidence: 87%
“…Apart from the enrichment of self-contained flavoring substances, the additives could also introduce new aroma components into CTLs. Coffee and cocoa contain abundant caffeine and theobromine, respectively, which give tobacco leaves fragrant aroma of coffee, cocoa, and nut (Gutierrez et al, 2022;Mostafa, 2022). It is consistent with the results of sensory quality.…”
Section: Aroma Components Analysissupporting
confidence: 87%
“…As shown in Figure 2b-2c, TN content increased from 3.83% (T1) to 5.05% (T2) and 4.59% (T3), while alkaloid content increased from 4.62% (T1) to 5.90% (T2) and 5.11% (T3). According to previous reports, abundant caffeine, theophylline, and theobromine could be found in coffee and cocoa, which could be converted to various aroma components of furan and pyrazine (Mejía et al, 2021;Mostafa, 2022;Chavez et al, 2022). Therefore, the enrichment of alkaloid in CTLs fermented with coffee and cocoa would promote the improvement of aroma quantity.…”
Section: Conventional Chemical Compositions Analysismentioning
confidence: 97%
“…By contrast, the contents of TS and RS in T2 and T3 groups were improved. It was reported that high concentration of carbohydrates was naturally present in coffee and cocoa (Lorenzo et al, 2022;Mostafa, 2022). Thus, CTLs fermented with coffee and cocoa would show a relatively good performance on the sweetness and aroma richness.…”
Section: Conventional Chemical Compositions Analysismentioning
confidence: 99%
“…This concentration range is low compared to the current study. Studies conducted in Saudi Arabia [35] and in Egypt [36] found the amount of caffeine in some energy drinks to be higher than that indicated on the label. In contrast, in our study, as in a study in Spain [37], the measured concentrations of caffeine (7.6 to 29.4 mg/100 mL) were below the ones mentioned on the label in all tested EDs.…”
Section: Discussionmentioning
confidence: 88%